Scratch-resistant anti-reflection glass product with optical property
By pretreating the glass substrate and lanthanum source treatment, a modified glass substrate is formed, and combined with nanofiber dispersion spraying technology, the problems of poor adhesion and insufficient hardness of the anti-reflection film are solved, and efficient anti-reflection and scratch resistance are achieved.
Patent Information
- Application Number
- CN202411628290.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-28
AI Technical Summary
The anti-reflective film has poor adhesion between the anti-reflective film and the glass matrix, and the anti-reflective film has low hardness and is susceptible to scratches and wear, which affects the anti-reflective performance of the glass.
By surface pretreatment and lanthanum source treatment on the glass substrate, a modified glass substrate is formed and impregnated into the composition to cure to form a double-layer anti-reflective coating. Then, the deacetylated nanofiber dispersion liquid is sprayed onto the glass surface to form a third layer of anti-reflective fiber membrane to enhance the scratch resistance and anti-reflective properties of the glass.
The light transmittance and scratch resistance of anti-reflective glass products are improved, the bonding force between the anti-reflective coating and the glass substrate is enhanced, the coating is avoided, and the anti-reflective and wear resistance of the glass is significantly improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of optical elements, in particular to a scratch-resistant anti-reflection glass product with optical properties. Background Art
[0002] The glass matrix has excellent transparency, chemical stability and mechanical strength, and can provide good support and protection for optical functional materials. The glass matrix can realize the integration of multiple functions, improve device performance and efficiency, and is expected to be used in transparent optoelectronic devices, such as lighting displays, touch screens, transparent circuits, etc.; since the glass matrix will inevitably reflect, affecting its use in optical devices, therefore, the surface of the glass matrix is covered with one or more layers of coatings with excellent anti-reflection function to form anti-reflective glass products. These coatings can effectively reduce the generation of reflected light, improve the transmittance of light, and enable light to better penetrate the glass to achieve anti-reflection effects, which are used to protect key components inside electronic products, including mobile devices such as smart phones, players and tablets and other optical devices. In addition, once the anti-reflective glass products have obvious scratches, the light scattering of the anti-reflective glass products will be enhanced, resulting in a significant decrease in the brightness, clarity and contrast of the displayed image and the sensory quality of the display. A certain degree of transparency, scratch resistance and wear resistance are also required.
[0003] Using glass as the substrate and coating the glass surface with an anti-reflection film can effectively reduce light reflection and increase light transmittance. However, the adhesion between the anti-reflection film and the glass substrate is poor, which causes the anti-reflection film to easily fall off. In addition, the anti-reflection film has a low hardness and is easily scratched and worn, affecting the anti-reflection performance of the glass. Summary of the invention
[0004] The invention provides a scratch-resistant anti-reflection glass product with optical properties, which solves the problems of poor adhesion between an anti-reflection film and a glass substrate and low hardness of the anti-reflection film being easily scratched and worn.
[0005] The technical solution of the present invention: A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Pre-treat the surface of the glass substrate, immerse it in a lanthanum source, stir and react, and obtain a modified glass substrate.
[0006] S2. Immerse the modified glass substrate in the composition, take it out, and solidify it to obtain an anti-reflection glass substrate.
[0007] S3. Spray the deacetylated nanofiber dispersion onto the surface of the anti-reflection glass substrate, and obtain a scratch-resistant anti-reflection glass product after heating and drying.
[0008] The composition is obtained by reacting nano silicon nitride, ammonium molybdate tetrahydrate and thiourea and then mixing with silicon dioxide sol.
[0009] Furthermore, in step S1, the glass substrate is selected from any one of soda-lime glass, aluminosilicate glass, borosilicate glass, and K9 glass.
[0010] Furthermore, in step S2, the curing temperature is 70-90°C, and the curing time is 2-5 minutes.
[0011] Furthermore, in step S2, the immersion time is 20-30 minutes.
[0012] Furthermore, in step S3, the heating and drying temperature is 80-120° C., and the heating and drying time is 2-5 hours.
[0013] Further, in step S3, a RH-CP0.3 spray gun is selected for spraying.
[0014] Further, in step S1, the modified glass substrate is specifically prepared by the following steps: A1. After washing the glass substrate with deionized water and anhydrous ethanol, the substrate was placed in a mixture of sulfuric acid and hydrogen peroxide, and ultrasonically treated for 13-17 min at an ultrasonic power of 280-320 W, removed, washed, and dried to obtain a pretreated glass substrate; A2. Add lanthanum nitrate to deionized water and stir to obtain a lanthanum source. Immerse the pretreated glass substrate in the lanthanum source and stir. Place the pretreated glass substrate in a 95-105°C water bath. Add 25-28% ammonia water to adjust the pH to 7.5-8.5. Stir for 1-2 hours. Take out and cool to room temperature. Filter, wash and dry to obtain a modified glass substrate.
[0015] Furthermore, in the above-mentioned reaction A1, sulfuric acid and hydrogen peroxide are used to clean the glass substrate, which can remove organic pollutants on the surface of the glass substrate and make the surface of the glass substrate rich in hydroxyl groups, which can interact with lanthanum ions in the lanthanum source and serve as sites for synthesizing lanthanum hydroxide nanorods.
[0016] Furthermore, during the above-mentioned A2 reaction process, the surface of the pretreated glass substrate contains a large number of hydroxyl structures, which can combine with the lanthanum ions in the lanthanum source, so that the lanthanum ions are deposited on the surface of the pretreated glass substrate. The reaction is carried out at 95-105°C. Ammonia water is a precipitant, which can combine with the lanthanum ions deposited on the surface of the pretreated glass substrate to form a lanthanum hydroxide precipitate. As the reaction proceeds, the lanthanum hydroxide crystallizes and grows, collides with each other, and forms a nanorod-like structure, thereby realizing the in-situ synthesis of lanthanum hydroxide nanorods on the surface of the glass substrate.
[0017] Furthermore, in step A1, the ratio of sulfuric acid to hydrogen peroxide is (30-40) mL:(10-20) mL.
[0018] Furthermore, in step A2, the ratio of the lanthanum nitrate to deionized water is (0.3-0.7) g: (90-110) mL.
[0019] Further, in step S2, the composition is specifically prepared by the following steps: B1. Add nano silicon nitride and sodium dodecylbenzene sulfonate to deionized water, stir for 1-3h, add thiourea and ammonium molybdate tetrahydrate, continue stirring for 1-3h to obtain a mixture, transfer the mixture to a reaction kettle, stir and react at 210-230°C for 6-8h, cool to room temperature, stand, take out the precipitate, wash and dry the precipitate to obtain a core-shell material; B2. Add the core-shell material to ethanol, stir evenly, add silica sol, stir and mix at 280-320 rpm for 25-35 min to obtain a composition.
[0020] Furthermore, in the above-mentioned B1 reaction process, after the surface of the nano silicon nitride is treated with sodium dodecylbenzene sulfonate, the surface carries sulfonate ions, and reacts at 210-230°C, so that ammonium molybdate tetrahydrate decomposes to release molybdenum ions, which can be adsorbed on the surface of the nano silicon nitride treated with sodium dodecylbenzene sulfonate. Thiourea decomposes at high temperature to release sulfur elements, which react with molybdenum ions to undergo sulfurization reaction to form molybdenum disulfide crystal nuclei. The reaction continues, so that the molybdenum disulfide crystal nuclei grow, and molybdenum disulfide nanosheets are formed on the surface of the nano silicon nitride to form core-shell materials.
[0021] Furthermore, during the above B2 reaction, the molybdenum disulfide nanosheets on the surface of the core-shell material contain a large number of hydroxyl structures, which can be chemically bonded with the silanols contained in the silica sol, so that the core-shell material is uniformly dispersed in the silica sol system to form a composite.
[0022] Furthermore, in step B1, the dosage ratio of the nano silicon nitride, sodium dodecylbenzene sulfonate, deionized water, thiourea, and ammonium molybdate tetrahydrate is (0.1-0.2) g: (0.1-0.14) g: (45-55) mL: (0.8-1) g: (0.5-0.7) g.
[0023] Furthermore, in step B2, the ratio of the core-shell material, ethanol and silica sol is (2-3) g: (15-25) mL: (13-17) g.
[0024] Furthermore, the silica sol is prepared by mixing tetraethyl orthosilicate, ethanol, deionized water, and hydrochloric acid in a dosage ratio of (2-3) g: (40-50) mL: (5-7) mL: (0.4-0.5) g.
[0025] Further, in step S3, the deacetylated nanofiber dispersion is prepared by the following steps: Chitosan was added to a 34-36% sodium hydroxide aqueous solution, stirred for reaction, cooled to room temperature, 35-37% acetic acid aqueous solution was added to adjust the pH to 3-4, and ultrasonic treatment was performed at a power of 550-600 W for 30-40 minutes to obtain a deacetylated nanofiber dispersion.
[0026] Furthermore, during the above reaction process, chitin is treated with sodium hydroxide to hydrolyze the amide bonds in the chitin nanofibers, thereby separating the acetyl groups. After ultrasonic treatment, the huge energy generated by the ultrasound can destroy the hydrogen bonds and van der Waals forces between the chitin nanofibers, thereby dissociating the chitin fiber bundles into chitin nanofibers and forming a chitin nanofiber dispersion carrying amino groups.
[0027] Furthermore, the chitosan and sodium hydroxide aqueous solution are used in a ratio of (1-2) g: (25-35) mL Furthermore, the deacetylated nanofibers have a diameter of 10-30 nm and a length of 1-1.2 μm.
[0028] The present invention has the following beneficial effects: (1) In the technical solution of the present invention, the glass substrate is cleaned with sulfuric acid and hydrogen peroxide to remove organic pollutants on the surface of the glass substrate, and at the same time, the surface of the glass substrate is enriched with hydroxyl groups, which can interact with lanthanum ions in the lanthanum source and serve as sites for synthesizing lanthanum hydroxide nanorods; lanthanum hydroxide nanorods are in situ synthesized on the surface of the pretreated glass substrate, so that the lanthanum hydroxide nanorods form a single-layer anti-reflection film on the surface of the glass substrate, which has high porosity and shows excellent anti-reflection properties, can reduce the reflection of the glass, and improve the light transmittance. The lanthanum hydroxide nanorods have a high bonding force with the glass substrate, thereby preventing the lanthanum hydroxide nanorods from falling off. In addition, the lanthanum hydroxide nanorods formed on the surface of the glass substrate give the glass substrate a better rough surface, thereby increasing the bonding force with the composition.
[0029] (2) In the technical solution of the present invention, the composition is applied to the surface of the modified glass substrate to form a double-layer anti-reflection coating on the surface of the glass substrate, which can increase the light transmittance and scratch resistance of the glass; the composition also includes core-shell nanomaterials and silica sol, the core-shell nanomaterials are made of molybdenum disulfide nanosheets formed on the surface of nano-silicon nitride, which can reduce light reflection and improve light transmittance, and the surface of the core-shell material has dense petal-shaped molybdenum disulfide flakes, which increases the contact area with light, can better receive the light reflected by the glass matrix, and reduce the reflection of light, and the formed core-shell material plays the role of bearing and "rolling bearing" on the surface of the glass matrix, enhancing The wear resistance and hardness of the glass matrix are improved, thereby enhancing the scratch resistance; the core-shell material is evenly dispersed in the silica sol system, and the hydroxyl groups contained on the surface of the core-shell material can be combined with the silanol groups contained in the silica sol through chemical bonds, thereby increasing the cross-linking density of the silica sol and improving the mechanical strength of the silica sol. The core-shell material is coated on the surface of the modified glass substrate, thereby enhancing the strength of the glass substrate. The silica sol has good fluidity and can be filled into the gaps of the lanthanum hydroxide nanorods on the surface of the modified glass substrate, so that the core-shell material is evenly coated on the surface of the glass substrate, and the bonding force with the modified glass substrate is increased, thereby enhancing the anti-reflection and scratch resistance.
[0030] (3) In the technical solution of the present invention, the deacetylated nanofiber dispersion is sprayed onto the surface of the anti-reflection glass substrate as the third layer of anti-reflection fiber film. On the one hand, the chitosan nanofibers construct a non-spherical nanoparticle anti-reflection coating to increase the light transmittance of the glass substrate and reduce reflection. On the other hand, the chitosan nanofiber dispersion with positive charge on the surface is sprayed onto the surface of the anti-reflection glass. The chitosan nanofibers with positive charge can be electrostatically bonded to the silanol groups in the silica layer on the surface of the anti-reflection glass, so that the anti-reflection fiber film is tightly bonded to the anti-reflection glass, thereby increasing the bonding force between the anti-reflection film and the glass and preventing the anti-reflection performance from falling off.
[0031] (4) In the technical solution of the present invention, by forming three layers of anti-reflection coating on the surface of the glass substrate, the reflection of light on the glass surface can be better reduced, the transmittance of light can be increased, the visual effect can be enhanced, and the application field of glass in optical devices can be broadened. In addition, the three layers of anti-reflection coating are tightly combined with the surface of the glass substrate and have excellent anti-reflection and scratch resistance. DETAILED DESCRIPTION
[0032] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0033] The raw materials used in the examples of the present invention are as follows, and all reagents used are of analytical grade.
[0034] Among them, nano silicon nitride: particle size is 50-60nm, Xi'an Qiyue Biotechnology Co., Ltd.
[0035] The deacetylated nanofibers have a diameter of 10-30 nm and a length of 1-1.2 μm.
[0036] The glass substrate is selected from aluminosilicate glass, with a thickness of 0.3-0.5 μm, a length and a width of 25×15 mm, and is purchased from Changzhou Yongjie High Temperature Resistant Glass Products Factory.
[0037] Example 1 A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Pre-treat the surface of aluminosilicate glass, immerse it in a lanthanum source, stir and react, and obtain a modified glass substrate.
[0038] S2. The modified glass substrate is immersed in the composition for 20 minutes, taken out, and cured at 70° C. for 2 minutes to obtain an anti-reflection glass substrate.
[0039] S3. Spray 10 mL of the deacetylated nanofiber dispersion onto the surface of the anti-reflective glass substrate, heat and dry at 80° C. for 2 h to obtain a scratch-resistant anti-reflective glass product, wherein a RH-CP0.3 spray gun is selected for spraying.
[0040] The modified glass substrate is specifically prepared by the following steps: A1. After washing the aluminosilicate glass with deionized water and anhydrous ethanol for 10 minutes, place it in a mixture of 30 mL of sulfuric acid and 10 mL of hydrogen peroxide, and ultrasonically treat it for 13 minutes at an ultrasonic power of 280 W. Then take it out, wash it with deionized water 3 times, wash it with ethanol 3 times, and dry it in an oven at 60°C for 10 minutes to obtain a pretreated glass substrate.
[0041] A2. Add 0.3 g of lanthanum nitrate to 90 mL of deionized water and stir until dissolved to obtain a lanthanum source. Immerse the pretreated glass substrate in the lanthanum source and stir for 20 minutes. Place it in a 95°C water bath and add 25% ammonia water to adjust the pH to 7.5. Stir for 1 hour, take it out, cool to room temperature, filter it, wash it with deionized water three times, and dry it in a 90°C oven for 10 minutes to obtain a modified glass substrate.
[0042] The composition is specifically prepared by the following steps: B1. Add 0.1 g of nano silicon nitride and 0.1 g of sodium dodecylbenzene sulfonate to 45 mL of deionized water, stir for 1 h, add 0.8 g of thiourea and 0.5 g of ammonium molybdate tetrahydrate, continue stirring for 1 h to obtain a mixture, transfer the mixture to a reactor, stir and react at 210 ° C for 6 h, cool to room temperature, let stand, take out the precipitate, wash the precipitate with deionized water 3 times, wash with ethanol 5 times, and dry in an oven at 60 ° C for 1 h to obtain a core-shell material.
[0043] B2. Add 2 g of core-shell material to 15 mL of ethanol, stir evenly, add 13 g of silica sol, stir and mix at 280 rpm for 25 min to obtain a composition, wherein the silica sol is prepared by mixing tetraethyl orthosilicate, ethanol, deionized water, and hydrochloric acid in a dosage ratio of 2 g:40 mL:5 mL:0.4 g.
[0044] The deacetylated nanofiber dispersion is specifically prepared by the following steps: 1 g of chitosan was added to 25 mL of 34% sodium hydroxide aqueous solution, stirred and reacted at 90°C for 4 h, cooled to room temperature, and 35% acetic acid aqueous solution was added to adjust the pH to 3. Ultrasonic treatment was performed at a power of 550 W for 30 min to obtain a deacetylated nanofiber dispersion.
[0045] Example 2 A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Pre-treat the surface of aluminosilicate glass, immerse it in a lanthanum source, stir and react, and obtain a modified glass substrate.
[0046] S2. The modified glass substrate is immersed in the composition for 25 minutes, taken out, and cured at 100° C. for 3 minutes to obtain an anti-reflection glass substrate.
[0047] S3. Spray 10 mL of the deacetylated nanofiber dispersion onto the surface of the anti-reflective glass substrate, heat and dry at 100° C. for 3 h to obtain a scratch-resistant anti-reflective glass product, wherein an RH-CP0.3 spray gun is selected for spraying.
[0048] The modified glass substrate is specifically prepared by the following steps: A1. After washing the aluminosilicate glass with deionized water and anhydrous ethanol for 10 minutes, the aluminosilicate glass was placed in a mixture of 35 mL of sulfuric acid and 15 mL of hydrogen peroxide, and ultrasonically treated for 15 minutes at an ultrasonic power of 300 W. The aluminosilicate glass was taken out, washed with deionized water for 3 times, washed with ethanol for 3 times, and dried in an oven at 60°C for 10 minutes to obtain a pretreated glass substrate.
[0049] A2. Add 0.5 g of lanthanum nitrate to 100 mL of deionized water and stir until dissolved to obtain a lanthanum source. Immerse the pretreated glass substrate in the lanthanum source and stir for 20 minutes. Place it in a 100°C water bath and add 27% ammonia water to adjust the pH to 8. Stir for 1.5 hours, take it out, cool it to room temperature, filter it, wash it 3 times with deionized water, and dry it in a 90°C oven for 10 minutes to obtain a modified glass substrate.
[0050] The composition is specifically prepared by the following steps: B1. Add 0.15 g of nano silicon nitride and 0.12 g of sodium dodecylbenzene sulfonate to 50 mL of deionized water, stir for 2 h, add 0.9 g of thiourea and 0.6 g of ammonium molybdate tetrahydrate, continue stirring for 3 h to obtain a mixture, transfer the mixture to a reactor, stir and react at 220 ° C for 7 h, cool to room temperature, let stand, take out the precipitate, wash the precipitate with deionized water 3 times, wash with ethanol 5 times, and dry in an oven at 60 ° C for 1 h to obtain a core-shell material.
[0051] B2. Add 2.5 g of core-shell material to 20 mL of ethanol, stir evenly, add 15 g of silica sol, stir and mix at 300 rpm for 30 min to obtain a composition, wherein the silica sol is prepared by mixing tetraethyl orthosilicate, ethanol, deionized water, and hydrochloric acid in a dosage ratio of 2.5 g: 45 mL: 6 mL: 0.3 g.
[0052] The deacetylated nanofiber dispersion is specifically prepared by the following steps: 1.5 g of chitosan was added to 30 mL of 35% sodium hydroxide aqueous solution, stirred and reacted at 90°C for 4 h, cooled to room temperature, and 36% acetic acid aqueous solution was added to adjust the pH to 3.5. The solution was ultrasonically treated at a power of 580 W for 35 min to obtain a deacetylated nanofiber dispersion.
[0053] Example 3 A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Pre-treat the surface of aluminosilicate glass, immerse it in a lanthanum source, stir and react, and obtain a modified glass substrate.
[0054] S2. The modified glass substrate is immersed in the composition for 30 minutes, taken out, and cured at 90° C. for 5 minutes to obtain an anti-reflection glass substrate.
[0055] S3. Spray 10 mL of the deacetylated nanofiber dispersion onto the surface of the anti-reflective glass substrate, heat and dry at 120° C. for 5 h to obtain a scratch-resistant anti-reflective glass product, wherein a RH-CP0.3 spray gun is used for spraying.
[0056] The modified glass substrate is specifically prepared by the following steps: A1. After washing the aluminosilicate glass with deionized water and anhydrous ethanol for 10 minutes, the aluminosilicate glass was placed in a mixture of 40 mL of sulfuric acid and 20 mL of hydrogen peroxide, and ultrasonically treated for 17 minutes at an ultrasonic power of 320 W. The aluminosilicate glass was taken out, washed with deionized water for 3 times, washed with ethanol for 3 times, and dried in an oven at 60°C for 10 minutes to obtain a pretreated glass substrate.
[0057] A2. Add 0.7 g of lanthanum nitrate to 110 mL of deionized water and stir until dissolved to obtain a lanthanum source. Immerse the pretreated glass substrate in the lanthanum source and stir for 20 minutes. Place it in a 105°C water bath and add 28% ammonia water to adjust the pH to 8.5. Stir for 2 hours, take it out, cool to room temperature, filter it, wash it 3 times with deionized water, and dry it in a 90°C oven for 10 minutes to obtain a modified glass substrate.
[0058] The composition is specifically prepared by the following steps: B1. Add 0.2 g of nano silicon nitride and 0.14 g of sodium dodecylbenzene sulfonate to 55 mL of deionized water, stir for 3 h, add 1 g of thiourea and 0.7 g of ammonium molybdate tetrahydrate, continue stirring for 3 h to obtain a mixture, transfer the mixture to a reactor, stir and react at 230 ° C for 8 h, cool to room temperature, let stand, take out the precipitate, wash the precipitate with deionized water 3 times, wash with ethanol 5 times, and dry in an oven at 60 ° C for 1 h to obtain a core-shell material.
[0059] B2. Add 3 g of core-shell material to 25 mL of ethanol, stir evenly, add 17 g of silica sol, stir and mix at 320 rpm for 35 min to obtain a composition, wherein the silica sol is prepared by mixing tetraethyl orthosilicate, ethanol, deionized water, and hydrochloric acid in a dosage ratio of 3 g:50 mL:7 mL:0.5 g.
[0060] The deacetylated nanofiber dispersion is specifically prepared by the following steps: 2 g of chitosan was added to 35 mL of 36% sodium hydroxide aqueous solution, stirred and reacted at 90°C for 4 h, cooled to room temperature, and 37% acetic acid aqueous solution was added to adjust the pH to 4. Ultrasonic treatment was performed at a power of 600 W for 40 min to obtain a deacetylated nanofiber dispersion.
[0061] Comparative Example 1 A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Immerse aluminosilicate glass into the composition for 30 minutes, take it out, and cure it at 90° C. for 5 minutes to obtain an anti-reflection glass substrate.
[0062] S2. Spray 10 mL of the deacetylated nanofiber dispersion onto the surface of the anti-reflective glass substrate, heat and dry at 120° C. for 5 h to obtain a scratch-resistant anti-reflective glass product, wherein a RH-CP0.3 spray gun is used for spraying.
[0063] The composition is specifically prepared by the following steps: B1. Add 0.2 g of nano silicon nitride and 0.14 g of sodium dodecylbenzene sulfonate to 55 mL of deionized water, stir for 3 h, add 1 g of thiourea and 0.7 g of ammonium molybdate tetrahydrate, continue stirring for 3 h to obtain a mixture, transfer the mixture to a reactor, stir and react at 230 ° C for 8 h, cool to room temperature, let stand, take out the precipitate, wash the precipitate with deionized water 3 times, wash with ethanol 5 times, and dry in an oven at 60 ° C for 1 h to obtain a core-shell material.
[0064] B2. Add 3 g of core-shell material to 25 mL of ethanol, stir evenly, add 17 g of silica sol, stir and mix at 320 rpm for 35 min to obtain a composition, wherein the silica sol is prepared by mixing tetraethyl orthosilicate, ethanol, deionized water, and hydrochloric acid in a dosage ratio of 3 g:50 mL:7 mL:0.5 g.
[0065] The deacetylated nanofiber dispersion is specifically prepared by the following steps: 2 g of chitosan was added to 35 mL of 36% sodium hydroxide aqueous solution, stirred and reacted at 90°C for 4 h, cooled to room temperature, and 37% acetic acid aqueous solution was added to adjust the pH to 4. Ultrasonic treatment was performed at a power of 600 W for 40 min to obtain a deacetylated nanofiber dispersion.
[0066] Comparative Example 2 A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Immerse aluminosilicate glass into a lanthanum source, stir and react to obtain a modified glass substrate.
[0067] S2. The modified glass substrate is immersed in the composition for 30 minutes, taken out, and cured at 90° C. for 5 minutes to obtain an anti-reflection glass substrate.
[0068] S3. Spray 10 mL of the deacetylated nanofiber dispersion onto the surface of the anti-reflective glass substrate, heat and dry at 120° C. for 5 h to obtain a scratch-resistant anti-reflective glass product, wherein a RH-CP0.3 spray gun is used for spraying.
[0069] The modified glass substrate is specifically prepared by the following steps: Add 0.7 g of lanthanum nitrate to 110 mL of deionized water and stir until dissolved to obtain a lanthanum source. Immerse the aluminosilicate glass in the lanthanum source and stir for 20 minutes. Place it in a 105°C water bath and add 28% ammonia water to adjust the pH to 8.5. Stir for 2 hours, take it out, cool it to room temperature, filter it, wash it with deionized water three times, and dry it in a 90°C oven for 10 minutes to obtain a modified glass substrate.
[0070] The composition is specifically prepared by the following steps: B1. Add 0.2 g of nano silicon nitride and 0.14 g of sodium dodecylbenzene sulfonate to 55 mL of deionized water, stir for 3 h, add 1 g of thiourea and 0.7 g of ammonium molybdate tetrahydrate, continue stirring for 3 h to obtain a mixture, transfer the mixture to a reactor, stir and react at 230 ° C for 8 h, cool to room temperature, let stand, take out the precipitate, wash the precipitate with deionized water 3 times, wash with ethanol 5 times, and dry in an oven at 60 ° C for 1 h to obtain a core-shell material.
[0071] B2. Add 3 g of core-shell material to 25 mL of ethanol, stir evenly, add 17 g of silica sol, stir and mix at 320 rpm for 35 min to obtain a composition, wherein the silica sol is prepared by mixing tetraethyl orthosilicate, ethanol, deionized water, and hydrochloric acid in a dosage ratio of 3 g:50 mL:7 mL:0.5 g.
[0072] The deacetylated nanofiber dispersion is specifically prepared by the following steps: 2 g of chitosan was added to 35 mL of 36% sodium hydroxide aqueous solution, stirred and reacted at 90°C for 4 h, cooled to room temperature, and 37% acetic acid aqueous solution was added to adjust the pH to 4. Ultrasonic treatment was performed at a power of 600 W for 40 min to obtain a deacetylated nanofiber dispersion.
[0073] Comparative Example 3 A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Pre-treat the surface of aluminosilicate glass, immerse it in a lanthanum source, stir and react, and obtain a modified glass substrate.
[0074] S2. The modified glass substrate is immersed in the composition for 30 minutes, taken out, and cured at 90° C. for 5 minutes to obtain an anti-reflection glass substrate.
[0075] S3. Spray 10 mL of the deacetylated nanofiber dispersion onto the surface of the anti-reflective glass substrate, heat and dry at 120° C. for 5 h to obtain a scratch-resistant anti-reflective glass product, wherein a RH-CP0.3 spray gun is used for spraying.
[0076] The modified glass substrate is specifically prepared by the following steps: A1. After washing the aluminosilicate glass with deionized water and anhydrous ethanol for 10 minutes, the aluminosilicate glass was placed in a mixture of 40 mL of sulfuric acid and 20 mL of hydrogen peroxide, and ultrasonically treated for 17 minutes at an ultrasonic power of 320 W. The aluminosilicate glass was taken out, washed with deionized water for 3 times, washed with ethanol for 3 times, and dried in an oven at 60°C for 10 minutes to obtain a pretreated glass substrate.
[0077] A2. Add 0.7 g of lanthanum nitrate to 110 mL of deionized water and stir until dissolved to obtain a lanthanum source. Immerse the pretreated glass substrate in the lanthanum source and stir for 20 minutes. Place it in a 105°C water bath and add 28% ammonia water to adjust the pH to 8.5. Stir for 2 hours, take it out, cool to room temperature, filter it, wash it 3 times with deionized water, and dry it in a 90°C oven for 10 minutes to obtain a modified glass substrate.
[0078] The composition is specifically prepared by the following steps: 3 g of nano silicon nitride was added to 25 mL of ethanol, stirred evenly, and 17 g of silica sol was added, and stirred and mixed at 320 rpm for 35 min to obtain a composition, wherein the silica sol was prepared by mixing tetraethyl orthosilicate, ethanol, deionized water, and hydrochloric acid in a dosage ratio of 3 g:50 mL:7 mL:0.5 g.
[0079] The deacetylated nanofiber dispersion is specifically prepared by the following steps: 2 g of chitosan was added to 35 mL of 36% sodium hydroxide aqueous solution, stirred and reacted at 90°C for 4 h, cooled to room temperature, and 37% acetic acid aqueous solution was added to adjust the pH to 4. Ultrasonic treatment was performed at a power of 600 W for 40 min to obtain a deacetylated nanofiber dispersion.
[0080] Comparative Example 4 A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Pre-treat the surface of aluminosilicate glass, immerse it in a lanthanum source, stir and react, and obtain a modified glass substrate.
[0081] S2. The modified glass substrate is immersed in the composition for 30 minutes, taken out, and cured at 90° C. for 5 minutes to obtain an anti-reflection glass substrate.
[0082] S3. Spray 10 mL of the deacetylated nanofiber dispersion onto the surface of the anti-reflective glass substrate, heat and dry at 120° C. for 5 hours to obtain a scratch-resistant anti-reflective glass product, wherein the spraying is performed using a RH-CP 0.3 spray gun.
[0083] The modified glass substrate is specifically prepared by the following steps: A1. After washing the aluminosilicate glass with deionized water and anhydrous ethanol for 10 minutes, the aluminosilicate glass was placed in a mixture of 40 mL of sulfuric acid and 20 mL of hydrogen peroxide, and ultrasonically treated for 17 minutes at an ultrasonic power of 320 W. The aluminosilicate glass was taken out, washed with deionized water for 3 times, washed with ethanol for 3 times, and dried in an oven at 60°C for 10 minutes to obtain a pretreated glass substrate.
[0084] A2. Add 0.7 g of lanthanum nitrate to 110 mL of deionized water and stir until dissolved to obtain a lanthanum source. Immerse the pretreated glass substrate in the lanthanum source and stir for 20 minutes. Place it in a 105°C water bath and add 28% ammonia water to adjust the pH to 8.5. Stir for 2 hours, take it out, cool to room temperature, filter it, wash it 3 times with deionized water, and dry it in a 90°C oven for 10 minutes to obtain a modified glass substrate.
[0085] The composition is specifically prepared by the following steps: B1. Add 0.2 g of nano silicon nitride and 0.14 g of sodium dodecylbenzene sulfonate to 55 mL of deionized water, stir for 3 h, add 1 g of thiourea and 0.7 g of ammonium molybdate tetrahydrate, continue stirring for 3 h to obtain a mixture, transfer the mixture to a reactor, stir and react at 230 ° C for 8 h, cool to room temperature, let stand, take out the precipitate, wash the precipitate with deionized water 3 times, wash with ethanol 5 times, and dry in an oven at 60 ° C for 1 h to obtain a core-shell material.
[0086] B2. Add 3 g of core-shell material into 100 mL of ethanol and stir evenly to obtain a composite.
[0087] The deacetylated nanofiber dispersion is specifically prepared by the following steps: 2 g of chitosan was added to 35 mL of 36% sodium hydroxide aqueous solution, stirred and reacted at 90°C for 4 h, cooled to room temperature, and 37% acetic acid aqueous solution was added to adjust the pH to 4. Ultrasonic treatment was performed at a power of 600 W for 40 min to obtain a deacetylated nanofiber dispersion.
[0088] Comparative Example 5 A scratch-resistant anti-reflective glass product with optical properties is prepared by the following steps: S1. Pre-treat the surface of aluminosilicate glass, immerse it in a lanthanum source, stir and react, and obtain a modified glass substrate.
[0089] S2. The modified glass substrate is immersed in the composition for 30 minutes, taken out, and cured at 90° C. for 5 minutes to obtain an anti-reflection glass substrate.
[0090] S3. Spray 10 mL of the deacetylated nanofiber dispersion onto the surface of the anti-reflective glass substrate, heat and dry at 120° C. for 5 h to obtain a scratch-resistant anti-reflective glass product, wherein a RH-CP0.3 spray gun is used for spraying.
[0091] The modified glass substrate is specifically prepared by the following steps: A1. After washing the aluminosilicate glass with deionized water and anhydrous ethanol for 10 minutes, the aluminosilicate glass was placed in a mixture of 40 mL of sulfuric acid and 20 mL of hydrogen peroxide, and ultrasonically treated for 17 minutes at an ultrasonic power of 320 W. The aluminosilicate glass was taken out, washed with deionized water for 3 times, washed with ethanol for 3 times, and dried in an oven at 60°C for 10 minutes to obtain a pretreated glass substrate.
[0092] A2. Add 0.7 g of lanthanum nitrate to 110 mL of deionized water and stir until dissolved to obtain a lanthanum source. Immerse the pretreated glass substrate in the lanthanum source and stir for 20 minutes. Place it in a 105°C water bath and add 28% ammonia water to adjust the pH to 8.5. Stir for 2 hours, take it out, cool to room temperature, filter it, wash it 3 times with deionized water, and dry it in a 90°C oven for 10 minutes to obtain a modified glass substrate.
[0093] The composition is specifically prepared by the following steps: B1. Add 0.2 g of nano silicon nitride and 0.14 g of sodium dodecylbenzene sulfonate to 55 mL of deionized water, stir for 3 h, add 1 g of thiourea and 0.7 g of ammonium molybdate tetrahydrate, continue stirring for 3 h to obtain a mixture, transfer the mixture to a reactor, stir and react at 230 ° C for 8 h, cool to room temperature, let stand, take out the precipitate, wash the precipitate with deionized water 3 times, wash with ethanol 5 times, and dry in an oven at 60 ° C for 1 h to obtain a core-shell material.
[0094] B2. Add 3 g of core-shell material to 25 mL of ethanol, stir evenly, add 17 g of silica sol, stir and mix at 320 rpm for 35 min to obtain a composition, wherein the silica sol is prepared by mixing tetraethyl orthosilicate, ethanol, deionized water, and hydrochloric acid in a dosage ratio of 3 g:50 mL:7 mL:0.5 g.
[0095] The carbon fiber dispersion is specifically prepared by the following steps: 2 g of carbon fiber was added into 100 mL of ethanol and stirred evenly to obtain a carbon fiber dispersion, wherein the carbon fiber had a diameter of 30 nm and a length of 1.2 μm.
[0096] The performance of the scratch-resistant anti-reflective glass products prepared in Examples 1-3 and Comparative Examples 1-5 is now tested.
[0097] Light transmittance and reflectance detection: The transmittance of the scratch-resistant anti-reflection glass product prepared above was measured using a TU-1900 UV-visible spectrophotometer, with the UV-visible light wavelength being 550nm; the reflectance of the scratch-resistant anti-reflection glass product prepared above was measured according to the CIE130-1998 standard.
[0098] Indentation hardness test: A nano indentation hardness test (Berkovich indenter, fixed nano indentation depth of 200 nm) was used to perform an indentation hardness test on the scratch-resistant anti-reflective glass product prepared above.
[0099] Elastic modulus test: The elastic modulus of the scratch-resistant anti-reflective glass product prepared above was tested according to the national standard GB / T 37780-2019.
[0100] Abrasion resistance test: Use 120 mesh quartz sandpaper, 20*20mm pressure head load 1.5kgF, rub the scratch-resistant anti-reflective glass product back and forth 10 times, and observe whether the surface of the product is damaged. See Table 1 below.
[0101] Table 1 Performance test of scratch-resistant anti-reflective glass products prepared in Examples 1-3 and Comparative Examples 1-5
[0102] It can be seen from the data in Table 1 that the scratch-resistant anti-reflective glass products prepared in Examples 1-3 have good anti-reflective properties and scratch resistance, and the anti-reflective coating is tightly bonded to the glass substrate. In Comparative Example 1, the modified glass substrate is replaced with a glass substrate, and the scratch-resistant anti-reflective glass product prepared has reduced anti-reflective properties and scratch resistance, proving that the in-situ synthesis of lanthanum hydroxide nanorods on the surface of the pretreated glass substrate shows excellent anti-reflective properties, and the formed lanthanum hydroxide nanorods give the glass substrate a good rough surface, increase the bonding force with the composition, and improve the scratch resistance.
[0103] In Comparative Example 2, the pretreated glass substrate is replaced with a modified glass substrate prepared from a glass substrate to prepare scratch-resistant anti-reflective glass products, and its anti-reflective properties and scratch resistance are reduced, proving that the surface of the pretreated glass substrate is rich in hydroxyl groups, and lanthanum hydroxide nanorods can be in situ synthesized on the surface of the pretreated glass substrate, so that the lanthanum hydroxide nanorods have a high bonding force with the glass substrate, thereby preventing the lanthanum hydroxide nanorods from falling off and affecting the performance of the glass substrate.
[0104] In Comparative Example 3, the core-shell material is replaced with a composition prepared by nano-silicon nitride to prepare scratch-resistant anti-reflective glass products, and its anti-reflection and scratch resistance are reduced, indicating that molybdenum disulfide nanosheets are formed on the surface of nano-silicon nitride, and its surface has dense petal-shaped molybdenum disulfide flakes, which increase the contact area with light, can better receive light reflected by the glass matrix, reduce the reflection of light, and the formed core-shell material plays the role of load-bearing and "rolling bearing" on the surface of the glass matrix, enhancing the wear resistance and hardness of the glass matrix.
[0105] In Comparative Example 4, the silica sol was replaced with a composition prepared with ethanol and used to prepare scratch-resistant anti-reflective glass products. The anti-reflective properties and scratch resistance of the glass products decreased, proving that the silica sol has good fluidity and can be filled into the gaps of lanthanum hydroxide nanorods on the surface of the modified glass substrate, so that the core-shell material is evenly coated on the surface of the glass substrate, and the bonding strength with the modified glass substrate is increased.
[0106] In Comparative Example 5, the deacetylated nanofiber dispersion was replaced with a carbon fiber dispersion and used to prepare scratch-resistant anti-reflective glass products. The anti-reflective properties and scratch resistance of the products decreased, proving that the deacetylated nanofibers, as the third layer of anti-reflective fiber film, increased the light transmittance of the glass substrate, and the positive charge carried by the deacetylated nanofibers was electrostatically bonded to the silanol group in the silica layer on the surface of the anti-reflective glass, so that the anti-reflective fiber film was tightly bonded to the anti-reflective glass.
[0107] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0108] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A scratch-resistant anti-reflective glass product having optical properties, characterized in that: Prepared by the following steps: S1. Pre-treating the surface of the glass substrate, immersing it in a lanthanum source, stirring the reaction, and obtaining a modified glass substrate; S2. The modified glass substrate is immersed in the composition, removed, and cured to obtain an anti-reflective glass substrate; The composition is obtained by reacting nano silicon nitride, ammonium molybdate tetrahydrate and thiourea, and then mixing with silica sol; S3. Spray the deacetylated nanofiber dispersion onto the surface of the anti-reflection glass substrate, and obtain a scratch-resistant anti-reflection glass product after heating and drying.
2. The scratch-resistant anti-reflective glass product with optical properties according to claim 1, characterized in that: In step S1, the modified glass substrate is specifically prepared by the following steps: A1. After washing the glass substrate with deionized water and anhydrous ethanol, the substrate was placed in a mixture of sulfuric acid and hydrogen peroxide, and ultrasonically treated for 13-17 min at an ultrasonic power of 280-320 W, removed, washed, and dried to obtain a pretreated glass substrate; A2. Add lanthanum nitrate to deionized water and stir to obtain a lanthanum source. Immerse the pretreated glass substrate in the lanthanum source and stir. Place the pretreated glass substrate in a 95-105°C water bath. Add 25-28% ammonia water to adjust the pH to 7.5-8.
5. Stir for 1-2 hours. Take out and cool to room temperature. Filter, wash and dry to obtain a modified glass substrate.
3. The scratch-resistant anti-reflective glass product with optical properties according to claim 2, characterized in that: In step A1, the ratio of sulfuric acid to hydrogen peroxide is (30-40) mL:(10-20) mL.
4. The scratch-resistant anti-reflective glass product with optical properties according to claim 2, characterized in that: In step A2, the ratio of lanthanum nitrate to deionized water is (0.3-0.7) g: (90-110) mL.
5. The scratch-resistant anti-reflective glass product with optical properties according to claim 1, characterized in that: In step S2, the composition is specifically prepared by the following steps: B1. Add nano silicon nitride and sodium dodecylbenzene sulfonate to deionized water, stir for 1-3h, add thiourea and ammonium molybdate tetrahydrate, continue stirring for 1-3h to obtain a mixture, transfer the mixture to a reaction kettle, stir and react at 210-230°C for 6-8h, cool to room temperature, stand, take out the precipitate, wash and dry the precipitate to obtain a core-shell material; B2. Add the core-shell material to ethanol, stir evenly, add silica sol, stir and mix at 280-320 rpm for 25-35 min to obtain a composition.
6. The scratch-resistant anti-reflective glass product with optical properties according to claim 5, characterized in that: In step B1, the dosage ratio of the nano silicon nitride, sodium dodecylbenzene sulfonate, deionized water, thiourea, and ammonium molybdate tetrahydrate is (0.1-0.2) g: (0.1-0.14) g: (45-55) mL: (0.8-1) g: (0.5-0.7) g.
7. The scratch-resistant anti-reflective glass product with optical properties according to claim 5, characterized in that: In step B2, the ratio of the core-shell material, ethanol and silica sol is (2-3) g: (15-25) mL: (13-17) g.
8. The scratch-resistant anti-reflective glass product with optical properties according to claim 1, characterized in that: In step S3, the deacetylated nanofiber dispersion is prepared by the following steps: Chitosan was added to a 34-36% sodium hydroxide aqueous solution, stirred for reaction, cooled to room temperature, 35-37% acetic acid aqueous solution was added to adjust the pH to 3-4, and ultrasonic treatment was performed at a power of 550-600 W for 30-40 minutes to obtain a deacetylated nanofiber dispersion.
9. The scratch-resistant anti-reflective glass product with optical properties according to claim 1, characterized in that: The silica sol is prepared by mixing tetraethyl orthosilicate, ethanol, deionized water and hydrochloric acid in a dosage ratio of (2-3) g: (40-50) mL: (5-7) mL: (0.4-0.5) g.
10. The scratch-resistant anti-reflective glass product with optical properties according to claim 1, characterized in that: The glass substrate is selected from any one of soda-lime glass, aluminosilicate glass, borosilicate glass, and K9 glass; the curing temperature is 70-90° C., and the curing time is 2-5 minutes; the heating and drying temperature is 80-120° C., and the heating and drying time is 2-5 hours.